Ideology on the Menu: The Role of GAL–TAN Ideologies in Shaping Dietary Behaviors - Morigi,Alessandro; Haidenberg Hemsani,Stephanie (2025)
Consumer choices around plant-based diets are increasingly shaped by political values, yet most research has focused on health, environmental, or economic motives, largely overlooking the role of ideology. While political ideology and political consumerism is well-documented in European contexts, there is limited understanding of how broader ideological orientations influence sustainable food behavior, particularly in regions such as Latin America. This thesis addresses that gap by examining how the GAL–TAN (Green-Alternative-Libertarian versus Traditional-Authoritarian-Nationalist) spectrum influences plant-based consumption and sustainability practices across Sweden, Italy, and Mexico. Using a convergent mixed-methods design, the study integrates a cross-national survey with nine semi-structured interviews with industry and academic experts. Quantitative findings reveal that GAL-oriented individuals are significantly more engaged in plant-based eating, political consumerism, and sustainability actions. However, these patterns vary across countries, with economic constraints and cultural framing playing a larger role in Mexico. Qualitative insights show how ethical motivations, affordability, and public discourse intersect with ideology, shaping both consumer behavior and market responses. By focusing on understudied regions, this thesis addresses key gaps in food politics research and highlights ideology as a critical, yet underexplored, driver of dietary change. It offers actionable insights for companies navigating ideologically diverse consumer markets.
Keywords: Political Consumerism; TAN-GAL Framework; Moral Foundation Theory; Consumer Behaviour; Plant-based Food Industry; Political Ideology